Wnt5a promotes VM formation by modulating the stemness and EMT progression of prostate cancer cell - Liu, Bide; Li, Xun; Wang, Shuheng; Jia, Hongliang; Zhang, Xiaoan; Dong, Qiang; Li, Jiuzhi (Translational oncology, 2025)
•Wnt5a was overexpressed in prostate cancer.•Wnt5a promotes vasculogenic mimicry formation in prostate cancer.•Wnt5a induces the process of epithelial-mesenchymal transition in prostate cancer.•Wnt5a activates the stemness of prostate cancer cells.•JNK/PI3K/Cdc42 signal pathway mediates Wnt5a induced vasculogenic mimicry formation. The incidence of prostate cancer (PCa) is increasing annually, making it the leading cause of tumor-related mortality in males. The available treatment options for metastatic PCa are limited. Vasculogenic mimicry (VM), an emerging phenomenon involving aggressive tumor cells, has a significant impact on patient survival. Misregulation of Wnt5a expression is commonly observed during cancer progression. However, there is a lack of comprehensive studies investigating the effects of Wnt5a on tumor VM formation. In this study, we demonstrate that alterations in wnt5a expression, either through gain or loss, have a significant influence on the formation of VM in tumor cells mediated by cell stemness and EMT progression. Further research has demonstrated that Wnt5a regulates the formation of VM through the PI3K/JNK signaling pathway. These experimental findings offer a novel avenue for the clinical management of prostate cancer. [Display omitted] The formation of vasculogenic mimicry (VM) can facilitate tumorigenesis and progression. Both the transdifferentiation of tumor cells into tumor stem cells and the epithelial-mesenchymal transition (EMT) of tumor cells can exacerbate VM formation. In our study, we discovered that Wnt5a specifically activates the JNK signaling pathway via PI3K/cdc42, thereby enhancing tumor cell stemness and EMT. This, in turn, exacerbates VM formation and promotes tumorigenesis and progression.